Pengukuran Kualitas Website Universitas Qamarul Huda Badaruddin Menggunakan Metode Webqual 4.0 - M Afriansyah; Valian Yoga Pudya Ardhana; Joni Saputra (LPPM Universitas Qamarul Huda Badaruddin, 2022)
Basically, some people will use website services to find quick and easy access to information. Website is the most commonly used online facility/service on the internet in addition to other services. For this reason, it is necessary to evaluate the quality of the website of the Qamarul Huda Badaruddin University. The framework used to measure the quality of website services in this study is WebQual 4.0 which is a development of Servqual which is usually used to measure service quality. the interests (expectations) of users on the quality of the uniqhba.ac.id website. Of the three variables, the greater contribution is found in the service interaction variable of 0.471 and the Sig value is obtained. 0.001 < = 0.1. So from the results of this study it can be translated that, evaluation of website quality needs to be done on usability dimensions or variables, respondents feel less in understanding or have difficulties in operating the website, and find it difficult to explore the website.